Excitation of high numbers harmonics by charge particles in a time-periodic electric field and a space-periodic potential - Buts, V.A.; Marekha, V.I.; Tolstoluzhsky, A.P. (Вопросы атомной науки и техники, 2006)
Regular and chaotic dynamics of a charged particle, which moves in an external time-periodic electrical field and in a field of space periodic potential, are investigated. We have obtained a system of integro-differential equations, which describes the non-linear self-consistent dynamics of excitation of electromagnetic waves by flows of charged particles. The analytical and numerical analysis of a full self-consistent set of equations is carried out. The results of this analysis qualitatively well agree with the experimental data.